Hydration Activity and Carbonation Characteristics of Dicalcium Silicate in Steel Slag: A Review - Hao Na; Yajun Wang; Xi Zhang; Junguo Li; Yanan Zeng; Pengyao Liu (Metals, 2021)
Dicalcium silicate is one of the main mineral phases of steel slag. Ascribed to the characteristics of hydration and carbonation, the application of slag in cement production and carbon dioxide sequestration has been confirmed as feasible. In the current study, the precipitation process of the dicalcium silicate phase in steel slag was discussed. Meanwhile, the study put emphasis on the influence of different crystal forms of dicalcium silicate on the hydration activity and carbonation characteristics of steel slag. It indicates that most of the dicalcium silicate phase in steel slag is the γ phase with the weakest hydration activity. The hydration activity of γ-C2S is improved to a certain extent by means of mechanical, high temperature, and chemical activation. However, the carbonation activity of γ-C2S is about two times higher than that of β-C2S. Direct and indirect carbonation can effectively capture carbon dioxide. This paper also summarizes the research status of the application of steel slag in cement production and carbon dioxide sequestration. Further development of the potential of dicalcium silicate hydration activity and simplifying the carbonation process are important focuses for the future.